Okra juice used for rapid wound healing through its bioadhesive and antioxidant capabilities - Biao Zhang; Yuanqiang Li; Kaijie Wu; Liqi Wei; Yining Chen; Yuan Zhang; Yiping Ren; Tianshu Zou; Pengcheng Yu; Hongxia Ma; Rui Chen; Xin Liu; et al. (Materials Today Bio)
Rapid wound healing is of great importance as it plays a crucial role in the body's response to injury or trauma. Biological adhesives are generally easy to apply, allowing for quick and efficient wound closure. In this study, we develop a natural biological adhesive derived from okra juice through a simple and environmentally friendly producing process. The strongest adhesion ability of this bioadhesive to wet tissue was 5.51 kPa, the ability to inhibit 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl radical, superoxide radical, hydroxyl radical, and hydrogen peroxide was 56.58 %, 49.94 %, 53.86 %, and 52.89 %, respectively, and the ability to promote cell proliferation was 181.46 %. The levels of pro-inflammatory tumor necrosis factor alpha (33.17 %) and Interleukin-6 (46.73 %) were significantly reduced. Both in vitro and in vivo evaluations indicate that it can effectively accelerate the healing process by sealing the wound, improving epithelial regeneration and angiogenesis, and alleviating inflammation. In addition, it has improved biocompatibility compared to commercial medical glue. Based on the favorable properties of the natural source, simple production process, and inherent nontoxicity, it shows potential as a medical bioadhesive for surgical procedures and emergency wound treatment.